Development of Booklet Learning Media and Its Role on Learning Interest of Islamic Elementary School Student - Dwi Setia Ningsih; Hanif Amrulloh; Nurul Aisyah; Masrurotul Mahmudah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to develop a Learning Media Booklet with the theme of Diversity of Professions and Their Roles, and to examine students' learning interest when using the booklet media. This research uses the Research and Development (R&D) Model developed by Brog & Gall, simplified into 7 stages, including (1) pre-survey, (2) initial planning, (3) development of initial product, (4) initial product expert testing, (5) revision of initial product, (6) main field trial, and (7) evaluation of final product. The instructional media trial was conducted at Ma'arif Bulusari Islamic Elementary School, Bumi Ratu Nuban Subdistrict, Central Lampung Regency, Lampung Province. The average ratings given by content experts, media experts, and language experts are 3.77, 3.66, and 3.85, respectively, which are categorized as very good, appropriate, and highly appropriate, in that order. The results of the student's learning interest test indicate a significant difference between using the instructional media booklet and not using the booklet, with an increase of 86.43% when using the instructional media booklet. Therefore, it can be concluded that the Diversity of Professions and Their Roles Learning Booklet meets the criteria for usability and can be tested in the third-grade class of Ma'arif Bulusari Islamic Elementary School.